2017
DOI: 10.1021/acsami.7b10891
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalytic Oxygen Reduction on NiWOx Solid Solution with Induced Oxygen Defects

Abstract: The continuous solid solution NiWO is successfully prepared by using precursor WO with plenty of oxygen defects. The NiWO nanoparticles are characterized by X-ray diffraction, high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, Raman spectroscopy, and X-ray absorption spectroscopy. The crystallographic phase of NiWO is stable and characterized by the same feature of the parent lattice WO even with various concentrations of dopant Ni which indicates the existence of oxygen defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…The electron-transfer numbers ( n ) were calculated (considering n = 4 for Pt/C) to be 4.13, 3.936, and 3.988 for the WO 3 ·H 2 O, WO 3 ·0.33H 2 O, and WO 3 ·2H 2 O phases, respectively. The results indicate that WO 3 ·2H 2 O and WO 3 ·0.33H 2 O follow a four-electron pathway for the complete reduction of O 2 to H 2 O. , The value obtained for n is similar to those of previous reports on W-based catalysts, such as n = 3.94 for Pt/NiWO x and n = 3.8 for an RGO/ZnWO 4 /Fe 3 O 4 nanocomposite . It is noted that the n value exceeding 4 (for the case of WO 3 ·H 2 O) could be related with the limitation of the K–L calculation method.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The electron-transfer numbers ( n ) were calculated (considering n = 4 for Pt/C) to be 4.13, 3.936, and 3.988 for the WO 3 ·H 2 O, WO 3 ·0.33H 2 O, and WO 3 ·2H 2 O phases, respectively. The results indicate that WO 3 ·2H 2 O and WO 3 ·0.33H 2 O follow a four-electron pathway for the complete reduction of O 2 to H 2 O. , The value obtained for n is similar to those of previous reports on W-based catalysts, such as n = 3.94 for Pt/NiWO x and n = 3.8 for an RGO/ZnWO 4 /Fe 3 O 4 nanocomposite . It is noted that the n value exceeding 4 (for the case of WO 3 ·H 2 O) could be related with the limitation of the K–L calculation method.…”
Section: Resultssupporting
confidence: 86%
“…At higher rotation rates, more O can diffuse to the electrode surface, resulting in larger reducing currents. The K−L plots obtained for different catalysts (Figure 4C) show a linear relationship between J k −1 and ω −1/2 , 50,51 The value obtained for n is similar to those of previous reports on W-based catalysts, such as n = 3.94 for Pt/NiWO x and n = 3.8 for an RGO/ZnWO 4 /Fe 3 O 4 nanocomposite. 52 It is noted that the n value exceeding 4 (for the case of WO 3 •H 2 O) could be related with the limitation of the K−L calculation method.…”
Section: Synthesis Of Wosupporting
confidence: 88%
“…This is suggestive of the nonstoichiometric features of the as-synthesized materials. Moreover, the composites of Pd–WO x , which has varied valence oxides on the surface, may be considered as another type of perovskite (ABO x ) in which A is Pd and B is W. In addition, in the Pd–W–O system, both PdO and WO x are potential catalysts for the electrocatalytic oxidation of alcohol and CO . The O 1s spectrum is shown in Figure h–j, and the peak observed at 524.9 eV is related to the Pd–O bonds.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several important conclusions can be drawn from the analysis of XPS images, so the calculated surface atomic O/W ratios of synthesized materials. Moreover, the composites of Pd−WO x , which has varied valence oxides on the surface, may be considered as another type of perovskite (ABO x ) in which A is Pd and B is W. In addition, in the Pd−W−O system, both PdO and WO x are potential catalysts for the electrocatalytic oxidation of alcohol and CO. 47 The O 1s spectrum is shown in Figure 5h−j, and the peak observed at 524.9 eV is related to the Pd−O bonds. The other three oxygen signals located at the binding energies of 527.9, 530.2, and 532.9 eV are related to the lattice O 2− (W−O bonds), hydroxyl (W−OH, tungsten bronze) species, and adsorbed water molecule (H 2 O), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…29 In addition, aliovalent ion doping creates a larger number of defects (such as oxygen vacancies) in the lattice and thereby changes the valence state of an element in an oxide, providing an opportunity to promote the adsorption of target reactants and the utilization of photoinduced electrons. 30,31 Wang et al reported that doping Mo atoms into WO x can promote photoinduced electron-hole pair separation and facilitate the transfer of photoinduced electrons from active sites to CO 2 , thereby increasing the efficiency of the photoreduction of CO 2 to CH 4 . 32 Xiong et al demonstrated that doping Mo 5+ into WO x nanowires can create massive defects (oxygen vacancies), resulting in the centers of Mo-W moieties being the active sites for the chemisorption of N 2 molecules.…”
Section: Introductionmentioning
confidence: 99%